1996
DOI: 10.1002/(sici)1097-4628(19960103)59:1<37::aid-app6>3.0.co;2-n
|View full text |Cite
|
Sign up to set email alerts
|

Effect of molecular weight and crystallinity on poly(lactic acid) mechanical properties

Abstract: SYNOPSISSeveral samples of poly(1actic acid) with different molecular weights and tacticity have been prepared, and some PLLA injection moulded specimens have been annealed to promote their crystallization. From the characterization data, poly(L-lactide) showed more interesting mechanical properties than poly(D,L-lactide), and its behavior significantly improves wit.h crystallization. In fact, annealed specimens possess higher values of tensional and flexural modulus of elasticity, Izod impact strength, and he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
263
1
6

Year Published

2001
2001
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 527 publications
(277 citation statements)
references
References 5 publications
7
263
1
6
Order By: Relevance
“…for 13 C methyl. Before Fourier transformation, the free induction decays were zero-filled twice in the 13 C dimension, and a shifted sine bell function was applied to both dimensions.…”
Section: Nmr Measurementmentioning
confidence: 98%
See 1 more Smart Citation
“…for 13 C methyl. Before Fourier transformation, the free induction decays were zero-filled twice in the 13 C dimension, and a shifted sine bell function was applied to both dimensions.…”
Section: Nmr Measurementmentioning
confidence: 98%
“…Thus, mechanical properties and heat resistance have been reported to depend on tacticity. 13,14 Recently, it was shown that tacticity could influence thermal stability, T m , T g , crystallinity, solution stability and polymer degradability in star-shaped PLA. 15,16 In addition, poly (L-lactic acid) and poly(D-lactic acid) could form a 1/1 stereocomplex, and the crystalline structure of the stereocomplex was quite different from that of poly(L-lactic acid) or poly(D-lactic acid).…”
Section: Introductionmentioning
confidence: 99%
“…It is known that the remodeling process during wound healing at the suture sites is helped by a moderate strain field on the part [13]. For this reason, a PLLA grade with an Elastic Modulus in the order of GPa could be too rigid for sutures applications [17].…”
Section: 2-mechanical Features Of the Blendsmentioning
confidence: 99%
“…A grade of entirely laevogyrate Poly(lactide) (PLLA) could also be used since its elastic modulus value is in the range of 4GPa [17].…”
mentioning
confidence: 99%
“…In this study, the proposed model does not include post-heating. However, it is suggested that post heating could enhance mechanical properties (Perego et al, 1996). To do so, some scaffolds with the struts' diameter of 700 and pore size of 350 micron are heated up to 3 more than crystallization temperature of the PLA which is about 115 .…”
Section: Investigation Of Post-heating Effect On the Elastic Modulusmentioning
confidence: 99%